2017
DOI: 10.1249/jsr.0000000000000342
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Evaluation of Nontraumatic Chest Pain in Athletes

Abstract: This article is a clinically relevant review of the existing medical literature relating to the assessment and diagnostic evaluation for athletes complaining of nontraumatic chest pain. The literature was searched using the following databases for the years 1975 forward: Cochrane Database of Systematic Reviews; CINAHL; PubMed (MEDLINE); and SportDiscus. The general search used the keywords chest pain and athletes. The search was revised to include subject headings and subheadings, including chest pain and prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 67 publications
0
2
0
1
Order By: Relevance
“…The prognosis is good, and there have been no reports of chronic pain, recurrence, chronic pericarditis, or tamponade. (5)(6)(7)(10)(11)(12)(13)(16)(17)(18)(19)(20)(21) ❚ CONCLUSION This case report describes the most common presentation of epipericardial fat necrosis in young healthy patients with pleuritic acute chest pain and negative emergency department work-up for more prevalent cardiovascular and pulmonary etiologies. Chest radiography revealed mild changes.…”
Section: ❚ Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The prognosis is good, and there have been no reports of chronic pain, recurrence, chronic pericarditis, or tamponade. (5)(6)(7)(10)(11)(12)(13)(16)(17)(18)(19)(20)(21) ❚ CONCLUSION This case report describes the most common presentation of epipericardial fat necrosis in young healthy patients with pleuritic acute chest pain and negative emergency department work-up for more prevalent cardiovascular and pulmonary etiologies. Chest radiography revealed mild changes.…”
Section: ❚ Discussionmentioning
confidence: 87%
“…(6) Despite the appropriate tendency for early discharge, some conditions may require further investigation and specific treatment. (7) Epipericardial fat necrosis usually presents as a newonset pleuritic chest pain in young healthy patients. (8,9) einstein (São Paulo).…”
Section: ❚ Discussionmentioning
confidence: 99%
“…Because of many clinical causes, it is often unable to judge the severity of the disease in time and may delay the treatment. It is found that chest pain is the main manifestation of cardiovascular diseases, such as acute myocardial infarction [1,2]. The incidence rate and mortality rate of acute myocardial infarction in China are increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Los principales motivos de consulta por "dolor en el pecho" en adultos jóvenes son de causa músculo-esquelética, seguido de causas pulmonares, psiquiátricas y cardíacas 3 .…”
Section: Introductionunclassified